Polypharmacy in nursing home residents with severe cognitive impairment: Results from the SHELTER Study. Issue 5 (10th December 2012) - Vetrano, Davide L.; Tosato, Matteo; Colloca, Giuseppe; Topinkova, Eva; Fialova, Daniela; Gindin, Jacob; van der Roest, Henriëtte G.; Landi, Francesco; Liperoti, Rosa; Bernabei, Roberto; Onder, Graziano; ,
Abstract: Objective: Pharmacological treatment of older adults with cognitive impairment represents a challenge for prescribing physicians, and polypharmacy is common in these complex patients. The aim of the current study is to assess prevalence and factors related to polypharmacy in a sample of nursing home (nursing home) residents with advanced cognitive impairment. Methods: We conducted a cross‐sectional analysis of 1449 nursing home residents with advanced cognitive impairment participating to the Services and Health for Elderly in Long Term Care (SHELTER) project, a study collecting information on residents admitted to 57 nursing home in eight countries. Data were collected using the International Resident Assessment Instrument (InterRAI) for long‐term care facilities. Polypharmacy status was categorized into three groups: nonpolypharmacy (zero to four drugs), polypharmacy (five to nine drugs), and excessive polypharmacy (≥10 drugs). Results: Polypharmacy was observed in 735 residents (50.7%) and excessive polypharmacy was seen in 245 (16.9%). Compared with nonpolypharmacy, excessive polypharmacy was associated directly with ischemic heart disease (odds ratio [OR], 3.68; 95% confidence interval [CI], 2.01–6.74), diabetes mellitus (OR, 2.66; 95% CI; 1.46–4.84), Parkinson's disease (OR, 2.84; 95% CI, 1.36–5.85), gastrointestinal symptoms (OR, 1.20; 95% CI, 1.43–3.39), pain (OR, 3.12; 95% CI, 1.99–4.89), dyspnea (OR, 2.57; 95% CI, 1.31–5.07), and recent hospitalization (OR, 2.56; 95% CI, 1.36–5.85). An inverse relation with excessive polypharmacy was shown for age (OR, 0.74; 95% CI, 0.59–0.93), activities of daily living disability (OR, 0.79; 95% CI, 0.63–0.99) and presence of a geriatrician on the nursing home staff (OR, 0.36; 95% CI, 0.20–0.64). Conclusion: Polypharmacy and excessive polypharmacy are common among nursing home residents with advanced cognitive impairment. Determinants of polypharmacy status includes not only comorbidities, but also specific symptoms, age, and functional status. A geriatrician in the facility is associated with lower prevalence of excessive polypharmacy.